Upaya Penyelesaian Malpraktek Medis dengan Menghadirkan PayungHukum Tindak Pidana Medis - Sulava Sururi Ramadhan (Wijayakusuma Law Review, 2022)
The development of health services and the demands of the community have an impact on changing the need forcompetence in primary health services which is one of the responsibilities of doctors. The emergence of variouscases involving patients with doctors in the legal realm then creates problems because it is very difficult todistinguish which is malpractice and which is negligence, accident, or failure by health workers. Until now,Indonesia does not yet have a nationally applicable medical professional standard. The absence of medicalprofessional standards is detrimental to the medical profession and society because professional standards fordoctors can be used as a tool to defend themselves for their medical actions, especially if medical practice harmspatients. This paper aims to analyze the importance of the presence of medical-legal protection as a guarantee ofthe protection of human rights for the community and medical personnel, especially doctors. The normativeresearch method uses a conceptual approach, a case approach, and a statutory approach. Many laws andregulations regulate malpractice but are unable to explain in detail the medical crime itself. So that a special lawshould be formed that explicitly regulates medical crimes so that the rules do not overlap and the resolution ofmedical cases can be resolved quickly and accurately.